Atypical development of configural face recognition in children with autism, Down syndrome and Williams syndrome. (25th July 2014) - Dimitriou, D.; Leonard, H. C.; Karmiloff‐Smith, A.; Johnson, M. H.; Thomas, M. S. C.
Abstract Background Configural processing in face recognition is a sensitivity to the spacing between facial features. It has been argued both that its presence represents a high level of expertise in face recognition, and also that it is a developmentally vulnerable process. Method We report a cross‐syndrome investigation of the development of configural face recognition in school‐aged children with autism, Down syndrome and Williams syndrome compared with a typically developing comparison group. Cross‐sectional trajectory analyses were used to compare configural and featural face recognition utilising the 'Jane faces' task. Trajectories were constructed linking featural and configural performance either to chronological age or to different measures of mental age (receptive vocabulary, visuospatial construction), as well as the Benton face recognition task. Results An emergent inversion effect across age for detecting configural but not featural changes in faces was established as the marker of typical development. Children from clinical groups displayed atypical profiles that differed across all groups. Conclusion We discuss the implications for the nature of face processing within the respective developmental disorders, and how the cross‐sectional syndrome comparison informs the constraints that shape the typical development of face recognition.